Educational Resources Availability and Utilization in Private and Public Secondary Schools in Kwara State, Nigeria - Omosibi, Abdurahman Suyuti; Atolagbe, Adedapo Adetiba; Ajao, Rasheed Lanre (International Journal of Educational Management, 2021)
The quantity of input devoted to education determines the level of output. This assertion has been a major issue of discussion among education stakeholders on whether the better performance of private compared to public secondary schoolstudents is as a results of educational resources available and their utilization. Thisstudy therefore investigated educational resources availability and utilization inprivate and public secondary schools in Kwara State. Descriptive survey design wasadopted for the study. The population for the study comprised all the 505 secondary schools in Kwara State. Stratified random and proportional sampling techniques were used to select 220 secondary schools (146 public and 74 private) for the study. Research instrument tagged “Educational Resources Checklist” (ERC) was used to obtain relevant data.The instrument was validated through face, content and construct validities by the researcher and three other lecturers in the Department of Educational Management. Descriptive statistics of percentage, ratio and rate were used to analyze the research questions raised in the study. Specifically, Time Utilization Rate (TUR), Space Utilization Rate (SUR), Global Utilization Rate (GUR) and Human Resources Utilization Rate (HRU) were used to determine the t utilization level of each of the resource under investigation. The findings of the studyshows that: there were shortage of physical resources in public secondary schools compared with private secondary schools in Kwara State; teachers were available in both public and private secondary schools; physical resources in private secondary schools were moderately utilized compared with public secondary schools; teachers were over utilized in private secondary schools compared with public secondary schools. The study concluded that the educational resources in Kwara State public secondary school are not enough to cater for the existing number of students, though fair in private secondary schools. Based on the findings of the study, it was recommended among others that: community should participate in provision of morephysical resources that will accommodate the existing number of students in the schools.